Ischemic-Free Liver Transplantation Reduces the Recurrence of Hepatocellular Carcinoma After Liver Transplantation - Tang, Yunhua; Wang, Tielong; Ju, Weiqiang; Li, Fangcong; Zhang, Qi; Chen, Zhitao; Gong, Jinlong; Zhao, Qiang; Wang, Dongping; Chen, Maogen; Guo, Zhiyong; He, Xiaoshun (Frontiers in Oncology, 2021)
Ischemia reperfusion injury (IRI) is an adverse factor for hepatocellular carcinoma (HCC) recurrence after liver transplantation. Ischemic-free liver transplantation (IFLT) is a novel transplant procedure that can largely reduce or even prevent IRI, but the clinical relevance of IFLT and the recurrence of HCC after liver transplantation are still unknown. This retrospective study compared survival outcomes, HCC recurrence, perioperative data and IRI severity following liver transplantation (LT). 30 patients received IFLT and 196 patients received conventional liver transplantation (CLT) were chosen for the entire cohort between June 2017 and August 2020. A 1:3 propensity score matching was performed, 30 IFLT recipients and 85 matched CLT patients were enrolled in propensity-matched cohorts. An univariate and multivariate Cox regression analysis was performed, and showed surgical procedure (CLT vs IFLT) was an independent prognostic factor (HR 3.728, 95% CI 1.172-11.861, P=0.026) for recurrence free survival (RFS) in HCC patients following liver transplantation. In the Kaplan–Meier analysis, the RFS rates at 1 and 3 years after LT in recipients with HCC in the IFLT group were significantly higher than those in the CLT group both in the entire cohort and propensity-matched cohort (P=0.006 and P=0.048, respectively). In addition, patients in the IFLT group had a lower serum lactate level, lower serum ALT level and serum AST level on postoperative Day 1. LT recipients with HCC in the IFLT group had a lower incidence of early allograft dysfunction than LT recipients with HCC in the CLT group. Histological analysis showed no obvious hepatocyte necrosis or apoptosis in IFLT group. In conclusion, IFLT can significantly reduce IRI damage and has the potential to be a useful strategy to reduce HCC recurrence after liver transplantation.